The use of linear ion trap for qualitative analysis of phytochemicals in Korean ginseng tea. (20th December 2012) - Stavrianidi, Andrey; Rodin, Igor; Braun, Arkady; Shpigun, Oleg
ABSTRACT: A new approach to qualitative analysis of ginsenosides in challenging matrices was developed on the basis of high‐performance liquid chromatography/tandem mass spectrometry. Using the extracts from samples of ginseng tea, the approach was validated. Analysis of extracts was carried out using a reversed‐phase chromatography with SB‐C18 sorbent. For compound identification, electrospray ionization and a quadrupole/linear ion trap mass‐spectrometer in different modes were used. A meticulous study of the fragmentation of ginsenosides in the linear ion trap and its application for analysis of these compounds was performed in this work. The accuracy of the identification was proven with standards of ginsenosides Rb1, Rg1, Re, Rf, Rd, Rb2, Rb3 and Rc. Copyright © 2012 John Wiley & Sons, Ltd.